LINC00665 promotes the progression of acute myeloid leukemia by regulating the miR-4458/DOCK1 pathway - Xiaoyu Yang (Nature Portfolio, 2021)
Abstract This study aimed to explore the role of LINC00665, miR-4458 and DOCK1 and their interactions in the development of acute myeloid leukemia (AML). The relative expression of LINC00665, miR-4458 and DOCK1 in AML samples was measured using qRT-PCR, and the protein level of DOCK1 in AML cell lines was examined using western blot. CCK8, BrdU, transwell, cell adhesion, and caspase-3 activity assays were carried out to evaluate the viability, proliferation, migration, adhesion, and apoptosis of AML cells, respectively. Luciferase reporter, RIP, and RNA pull-down assays were also performed to confirm the target relationship among LINC00665, miR-4458 and DOCK1. Findings revealed that LINC00665 and DOCK1 were aberrantly overexpressed in AML tissues and that the expression of miR-4458 was low in AML tissues. Silencing LINC00665 or DOCK1 presented significant restriction to the proliferation, migration and adhesion of AML cells. Apart from that, it was found that inhibiting miR-4458 could enhance the proliferation, migration and adhesion of AML cells but suppress the apoptosis of AML cells. Experimental results also indicated that LINC00665 exerted its positive function on AML cells by sponging miR-4458 and that miR-4458 influenced the progression of AML cells by targeting DOCK1 directly. Overall, this finding not only provided a novel molecular pathway for the diagnosis and treatment of AML but also showed that LINC00665 could enhance the progression of AML by regulating the miR-4458/DOCK1 pathway.